TECHNOLOGY-MEDIATED LESSON STUDY.A STEP -BY-STEP GUIDE (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This paper examines the integration of technology into educational environments, specifically focusing on its benefits and challenges in the classroom. Despite the familiarity students have with technology, many schools still rely on analog tools. By discussing the potential benefits of using technology, such as increasing student engagement and providing immediate feedback, as well as the barriers to implementing technology, such as financial constraints and hardware limitations, this paper aims to provide insight into how teachers and students can benefit from incorporating technology into the classroom.